(untitled) (Research, Society and Development, 2023)
This study aims to review the literature that deals with the use of biomonitors to assess air quality in Brazil. The integrative review that investigated the production of knowledge on the subject was used as a method. For this, Google Scholar, SciELO and the Brazilian Digital Library of Theses and Dissertations (BDTD) databases were used, establishing the period between 2019 and 2022 as a time frame. The search terms used were “biomonitoramento”, “biomonitor” and “bioindicador” for greater coverage of the topic and return of more representative results. We identified 68 Brazilian studies that met the initial inclusion criteria. Then, the works went through 3 filtering phases, having as elements of analysis: (i) titles, (ii) abstracts and conclusions and, finally, (iii) full texts. In the end, there were 6 studies that effectively dealt with the subject. After analyzing the scientific production, it was concluded that, despite the limitations due to some factors such as meteorological factors and those related to the physiology and anatomy of plants, biomonitors present good results when used to monitor air quality.